Obesity in Bulgarian patients with chronic obstructive pulmonary disease. (November 2013) - Dimov, Dimo; Tacheva, Tanya; Koychev, Atanas; Ilieva, Vanya; Prakova, Gospodinka; Vlaykova, Tatyana
It has been well defined that obesity is strongly linked with several respiratory symptoms and diseases, but no convincing evidence has been provided for chronic obstructive pulmonary disease (COPD). In the current study, we aim to assess the possible prevalence of obesity in patients with COPD in a cross-sectional case–control study of individuals from the region of Stara Zagora, Bulgaria, and to explore whether the body mass has some effect on the lung function of COPD patients. The study included 158 patients with COPD (Global Initiative for Chronic Obstructive Lung Disease (GOLD) II, III, and IV stages) and 123 individuals unaffected by the disease (control). A higher frequency of obesity compared to the controls (20.3%) was observed in patients with COPD (29.1%, p = 0.093), especially in those with GOLD II stage (37.7%, p = 0.009). Prevalence of obesity was highest in COPD GOLD II, followed by GOLD III and IV stages ( p = 0.068). When diabetes was considered as confounding factor, we found a significant prevalence of obesity in COPD patients than the controls with diabetes ( p = 0.031). Interestingly, there was a statistically significant moderate positive correlation between the body mass index and forced expiratory volume in one second as a percentage of predicted value in the whole patients' group ( R = 0.295, p = 0.0002) as well as in the subgroups of GOLD II ( R = 0.257, p = 0.024) and GOLD III COPD ( R = 0.259, p = 0.031).The results of our study propose that the increased body mass, particularly obesity is frequent comorbidity to COPD, especially to less severe diseases. Moreover, the results suggest that the higher body weight may provide some protection against the impairment of lung functions in patients with stable COPD.